Algunos componentes esteroidales del solanum havanense jacq - Basterrechea Rey, Mario J.; Ferrer Hernández, Anselmo; Calzadilla González, Míriam; Rodríguez Albelo, Marleny; Navarro Frómeta, Amado Enrique (CIENCIA ergo-sum, 2015)
--